Fiscal rules and the behavior of public investment in Latin America and the Caribbean: Towards growth-friendly fiscal policy? The case of Argentina - Daniel A. Artana; Cynthia Moskovits; Jorge Puig; Ivana Templado (Inter-American Development Bank (IDB), 2021)
This paper analyzes the implementation of Fiscal Rules (FR) in Argentina. Several clear attempts to establish a FR at the national level are identified. The analysis suggests that the environment matters. The only FR that was binding in the period was approved in 2004 during an economic boom, with the country under a program with the IMF and with high political support. During the world financial crisis the expenditure ceilings were relaxed, however, and current primary expenditures soared. Simulations show that a countercyclical fund could have been implemented even after reducing highly distorting taxes at the federal and provincial levels, and at the same time securing a high level of capital expenditure as a share of GDP, had Argentina complied with the 2004 FR. Moreover, an econometric exploration of the link between flexible FRs and public investment finds that a flexible FR helps to mitigate the negative effects of fiscal consolidations on provincial public investment. Based on the previous analysis, guidelines for a proposal for a FR in Argentina are provided.
Keywords: E32; E60; H12; H50; H54; 330; Fiscal rules; Public investment; Argentina